Single cell whole genome sequencing of high hyperdiploid acute lymphoblastic leukemia - Woodward, Eleanor; Yang, Minjun; Moura-Castro, Larissa Helena; van den Bos, Hilda; Gunnarsson, Rebeqa; Arvidsson, Linda Olsson; Spierings, Diana C. J.; Castor, Anders; Duployez, Nicolas; Zaliova, Marketa; Zuna, Jan; Johansson, Bertil; et al. (Lund University, 2022)
This dataset included 577 samples with high hyperdiploid acute lymphoblastic leukemia (ALL) that were collected from four different cohorts: the Division of Clinical Genetics, Lund University, Sweden, Department of Pediatric Hematology and Oncology, Second Faculty of Medicine, Charles University/University Hospital Motol, Prague, Czech Republic (Zaliova et al., 2016), Laboratory of Hematology, Centre Hospitalier Universitaire (CHU) Lille, Lille, France (Duployez et al., 2018), and The Therapeutically Applicable Research to Generate Effective Treatments (TARGET) program (NCBI dbGAP accession number phs00464). All samples were genotyped using either the Affymetrix SNP Array, Illumina's BeadArray platform or the whole genome/exome sequencing by the Illumina platform.  Nine high hyperdiploid ALL samples and one normal bone marrow sample were subjected to low pass single cell whole genome sequencing with the median sequencing coverage of 0.02x. Single nuclei in G0/G1 phase were isolated using a fluorescence-activated cell sorting (FACS) cytometer. DNA libraries were constructed and associated next-generation sequencing was carried out by European Research Institute for the Biology of Ageing (ERIBA), University of Groningen, University Medical Center Groningen, Groningen, The Netherlands. Further details regarding the DNA libraries construction are available by Bos et. al., 2019 (https://link.springer.com/protocol/10.1007/978-1-4939-8931-7_15). The dataset has been used for copy number aberrations analysis. The raw data file can be made available after applying for access and agreeing to the terms and conditions for use.
Keywords: Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik